Human behavior and its effect on oral biology: biocuitural observation - Etty Indriati, Etty Indriati (Universitas Gadjah Mada, 2002)
Human behavior, tradition, habit, and culture are closely associated with human biological condition, their health and sickness. Thus, humans habits and activities mimic in their health and sickness. Among human cultural traditions reviewed are coca-leaf chewing, betel-nut chewing, tobacco chewing, irradiation treatment in cancer patients, tooth-tool use related to task activities, tooth cleaning and palliative purposes, and gum chewing. Many literatures have shown that humans activities and habits have impact on their oral biology, ranging from gingival recession, hyperkeratosis of buccal mucosa, cervical-root caries on molar teeth, desquamation of tongue, approximal grooves, and leucoplakia on the oral mucosa. This review suggests that understanding a disease process requires knowledge of humans activities and cultural tradition due to the close association of culture and biology, behavior and health.Key words: habit, teeth, oral, biology, health